New two-phase and three-phase thermodynamic models for predicting wax precipitation in hydrocarbon mixtures - Sulaimon, A.A. (Elsevier B.V., 2022)
One of the major issues in flow assurance is the precipitation and subsequent deposition of paraffin wax in petroleum production systems. A new two-phase multicomponent thermodynamic model based on a continuous thermodynamic phase equilibria employing a three-parameter gamma distribution function has been developed to predict the wax appearance temperature (WAT), the amount of precipitated wax, and the wax content of crude oils. Also, a generalized three-phase multicomponent thermodynamic model based on the combined polymer and regular solution theories of mixtures as well as on equations of state (EOS) is presented. The model utilizes the solid-liquid-vapour phase equilibrium relations with some constraint functions. Furthermore, hinged on the regression analysis of published experimental data, a new set of molecular-weight-dependent thermodynamic propertiesâ correlations were developed and used to calculate the solid-liquid-equilibrium-ratios (KiS-L) for the individual component. The models were validated with data obtained from experiments conducted on 32 different hydrocarbon fluids from the Niger Delta, North Sea, Gulf of Mexico, East Asia, and Middle East fields. Results show that the gamma distribution parameters (Î±, Î², Î·) can be used to classify hydrocarbon mixtures into three categories: light oils or condensate, waxy oil or asphaltenic oils, and biodegraded oils. Analysis shows that when compared with experimental data, the two-phase thermodynamic model is reliable with the average absolute deviations (AAD) of 0.80 for paraffinic and waxy oils, 0.42 for paraffinic and waxy condensates, and 4.33 for paraffinic-asphaltenic and biodegraded oils. For the three-phase model, results show that the AAD for the paraffinic and waxy oils, paraffinic and waxy condensates, and biodegraded oils are 0.93, 1.03, and 4.88 respectively. However, the two models slightly overestimate the WAT for biodegraded crude oils. Nevertheless, the generalized thermodynamic models developed have proved to be effective for predicting the onset conditions for wax precipitation during petroleum production and processing. It will prove a helpful tool for the fast and accurate assessment of wax deposition tendencies of hydrocarbon mixtures. Â© 2021 Elsevier B.V.